The role of serum tryptase in the diagnosis and monitoring of pediatric mastocytosis: a single-center experience - Lange, Magdalena; Zawadzka, Agata; Schrörs, Stephanie; Słomka, Justyna; Ługowska-Umer, Hanna; Nedoszytko, Bogusław; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: In children, cutaneous mastocytosis (CM) is considered to be a benign disease associated with mast cell mediator-related symptoms. However, systemic mastocytosis (SM) and anaphylaxis may also occur. Since the basal serum tryptase (bsT) level reflects mast cell burden, its determination is recommended in the diagnosis and follow-up. Aim: To compare clinical presentation and the course of mastocytosis in children with normal and clearly elevated bsT levels as well as to assess its usefulness in the diagnosis and monitoring of the course of the disease. Material and methods: A retrospective analysis of 102 medical records of children with mastocytosis diagnosed and followed-up in the Gdansk Mastocytosis Center in 2014 was performed. Results: Maculopapular CM (MPCM) was diagnosed in 91 (89.22%) children, diffuse cutaneous mastocytosis (DCM) in 7 (6.86%) and mastocytoma in 4 (3.92%). The presence of flushing and bullous lesions was more frequent in children with bsT levels > 20 ng/ml in comparison with those who had bsT ≤ 20 ng/ml (p = 0.002 and p = 0.03, respectively). Anaphylaxis occurred in 2 MPCM children with bsT levels in normal ranges. In all of the 3 children with persistently and clearly elevated bsT levels, bone marrow biopsy revealed no mast cells infiltrates corresponding to SM. Conclusions: Although mastocytosis children with clearly elevated bsT levels frequently develop mediator-related symptoms, the occurrence of anaphylaxis in this age group may be difficult to predict. In pediatric cases with suspected SM, the bsT level is one of the crucial parameters considered before the decision on bone marrow biopsy.